Emergency medical technician EMT in action - Aehlert, Barbara (McGraw-Hill higher education, 2009)
Preparatory; Airway; Patient assessment; Medical-behavioral emergencies and obstetrics and gynecology; Trauma; Infants and children; Operations; Advanced airway (elective)